Dampak Struktur Modal dan Tata Kelola Perusahaan Terhadap Nilai Perusahaan - Budiadnyani, Ni Putu; Azizah, Wafid; Dewi, Putu Pande R. Aprilyani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Firm value is a crucial metric that reflects a company's performance and influences investor perceptions. This study aims to investigate the impact of capital structure and corporate governance on the firm value of food and beverage companies listed on the Indonesia Stock Exchange. This study used data from food and beverage companies in 2018 and 2021, with the sample determined through purposive sampling. Data analysis was conducted using multiple regression tests. The findings contribute to the understanding of how capital structure and corporate governance mechanisms, such as the audit committee and board of commissioners, can influence the value of companies in the food and beverage industry in Indonesia. The results of this study provide valuable insights for company management, investors, and policymakers in the food and beverage sector, highlighting the importance of optimizing capital structure and strengthening corporate governance practices to enhance firm value.